Conditional-GAN Based Data Augmentation for Deep Learning Task Classifier Improvement Using fNIRS Data - Wickramaratne, Sajila D.; Mahmud, Md.Shaad (Frontiers in Big Data, 2021)
Functional near-infrared spectroscopy (fNIRS) is a neuroimaging technique used for mapping the functioning human cortex. fNIRS can be widely used in population studies due to the technology's economic,non-invasive, and portable nature. fNIRS can be used for task classification, which is a crucial part of functioning with Brain-Computer Interfaces(BCIs). fNIRS data are multidimensional and complex, making them ideal for deep learning algorithms for classification. Deep Learning classifiers typically need a large amount of data to be appropriately trained without over-fitting. Generative networks can be used in such cases where a substantial amount of data is required. Still, the collection is difficult due to various constraints. Conditional Generative Adversarial Networks (CGAN) can generate artificial samples of a specific category to improve the accuracy of the deep learning classifier when the sample size is insufficient. The proposed system uses a CGAN with a CNN classifier to enhance the accuracy through data augmentation. Based on the fNIRS data patterns, the system can determine whether the subject's task is a Left Finger Tap, Right Finger Tap, or Foot Tap. The authors obtained a task classification accuracy of 96.67% for the CGAN-CNN combination.